2013
DOI: 10.1038/sc.2013.123
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on bowel management and the success rate of the various treatment modalities in spina bifida patients

Abstract: A systematic review on bowel management and the success rate of the various treatment modalities in spina bifida patients SV Velde, SV Biervliet, RD Bruyne and MV Winckel Study design: Systematic review. Objectives: To determine the different treatment modalities aimed at achieving fecal continence in spina bifida (SB) patients and their effectiveness. Setting: International literature. Method: Electronic databases were searched ('Pubmed', 'Web of science', 'CINAHL' and 'Cochrane') identifying studies publishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…11 Continence rates with these methods range from 67-80%, and positively impact quality of life. 39 Anterograde colonic enema through a surgical ostomy may also be recommended for select individuals, with resultant continence rates exceeding 80% and reduced need for medication or rectal maneuvers. 15 Despite the availability of effective regimens, only 24% of our population reported having an active bowel regimen program.…”
Section: Discussionmentioning
confidence: 99%
“…11 Continence rates with these methods range from 67-80%, and positively impact quality of life. 39 Anterograde colonic enema through a surgical ostomy may also be recommended for select individuals, with resultant continence rates exceeding 80% and reduced need for medication or rectal maneuvers. 15 Despite the availability of effective regimens, only 24% of our population reported having an active bowel regimen program.…”
Section: Discussionmentioning
confidence: 99%
“…According to a review by Velde et al ., pseudocontinence was achieved in 80% of patients using RCE . Although spina bifida was the underlying condition in the majority of patients pooled, miscellaneous conditions were considered.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of intestinal peristalsis, rectal sensation, and anal sphincter function often result in a mixed clinical presentation of constipation and bowel incontinence. 52 As with urinary incontinence, loss of bowel control affects QOL, interfering with social relations and self-esteem. A study by Rocque et al 36 found that children older than 5 years with SB and bowel incontinence had a significantly decreased health-related QOL than those with bowel control.…”
Section: Bowel Functionmentioning
confidence: 99%
“…12 However, this procedure should be reserved for patients in whom conservative medical management has failed, as it is associated with many complications, including stomal stenosis, stomal infection, and other stomal failures requiring revision. 44,52 Because a higher proportion of adult SB patients have undergone Malone creation, it is important for providers to recognize and treat these complications at an early stage to maintain continence.…”
Section: Bowel Functionmentioning
confidence: 99%